Status of the Golden Eagle Aquila chrysaetos in Sicily - Sara' M; BONDI', Salvatore; Giardina G; Saitta G; Surdo S; Zanca L. (Ciso, 2017)
In the present work, we review all the relevant information since the first Regional Atlas of breeding birds (Massa 1985), and we add field data on the species occurrence and site occupancy relative to the period January 2014-December 2016, in order to update the species’ status in Sicily.